Determination of the composition of fatty acids from tea seed oil - GUO Hua; ZHOU Jian-ping; LUO Jun-wu; TAN Hui-yuan; LIU Dong-min (浙江大学学报. 农业与生命科学版, 2010)
The composition analyses of lipids were conducted with the seeds from 24 varieties of tea plants. The lipids of the tea seeds were extracted from tea seed powder with methanol and chloroform. The methylated lipids were determined by gas chromatography (GC) equipped with 100 m × 0.25 mm capillary column. The results indicated that the lipids were composed of 20 fatty acids (FA) with 79% unsaturated fatty acids (UFA). The average content of monounsaturated fatty acids (MUFA) in FA was 51.06%, of which 96.4% was oleic acid. The average content of polyunsaturated fatty acids (PUFA) in FA was 27.86%, of which 98.6% was linoleic acid. The average content of saturated fatty acids (SFA) was 20.67%. The major components of SFA were palmitic acid (78.3%) and stearic acid (19.3%). In addition, tea seeds contained 0.144% trans-18:1, which might be a precursor of 9c, 11t-CLA in human. This conjugated linoleic acid might be one of the functional components related to the function of anticancer, anti-atherosclerosis, antibacterial, antivirus or regulation of immunity. The results above show that the composition of tea seeds lipids is coincided well with the modern standards for a healthy vegetable oil.